AMS Standing Committee on New Skills 2013: Follow-up-workshops 2013 - Wolfgang Bliem; Emanuel Van den Nest; Silvia Weiß; Gabriele Grün (Arbeitsmarktservice Österreich (AMS), 2014)
In October 2009, the Administrative Board of Public Employment Service Austria (AMS) set up an AMS Standing Committee on New Skills. Since that time, the Committee has continually initiated projects that aim to identify changes in needs for qualifications in collaboration with experts from companies. Based on these projects, the Committee develops continuing education and training (CET) programmes to make it easier for jobseekers to re-enter the world of work. These CET programmes are based on cluster-specific catalogues of modules that, since the autumn 2011, have become part of the AMS course plan and have since undergone further development and optimisation to ensure a continuous improvement of the target group-appropriate course design. This report aims to summarise the results of a follow-up phase in 2013, during which one workshop each was organised for the following eight company clusters (in alphabetical order): construction and building ecology; office and administration; chemistry and plastics; electrical engineering, electronics, telecommunications; energy and environmental engineering; commerce; machinery, motor vehicles, metal; tourism and wellness. – – Im Oktober 2009 wurde vom Verwaltungsrat des Arbeitsmarktservice Österreich (AMS) ein "AMS Standing Committee on New Skills" eingerichtet, das seither kontinuierlich Projekte initiiert, um gemeinsam mit ExpertInnen aus Unternehmen Veränderungen im Qualifikationsbedarf zu analysieren. Darauf aufbauend werden seitens des AMS Weiterbildungsangebote entwickelt (New-Skills-Kurse), die Arbeitsuchenden den Wiedereinstieg in die Beschäftigung erleichtern sollen. Grundlage für diese Weiterbildungen bilden clusterspezifische Modulkataloge, die seit Herbst 2011 Eingang in die Kursplanung des AMS finden und seither weiterentwickelt und optimiert werden, um die zielgruppenadäquate Gestaltung der Kursangebote laufend zu verbessern. Der vorliegende Bericht (= AMS report 105), der im Auftrag der Abt. Arbeitsmarktforschung und Berufsinformation des AMS Österreich vom Institut für Bildungsforschung der Wirtschaft (ibw) erstellt wurde, fasst die Ergebnisse einer Follow-up-Phase im Jahr 2013 zusammen, in der zu folgenden acht Unternehmensclustern je ein Workshop durchgeführt wurde: Bau und Bauökologie; Büro und Verwaltung; Chemie und Kunststoff; Elektrotechnik, Elektronik und Telekommunikation; Energie und Umwelttechnik; Handel; Maschinen, Kfz, Metall; Tourismus und Wellness.
Keywords: 330